Maternal Determinants of Low Birth Weight: A Case-Control Study - Naomi Hutasoit; Lasria Simamora; Polma Ria Metawati Panjaitan; Fiska Surya Nesa; Deanurista Perangin-angin (Jurnal Ners, 2026)
Low birth weight (LBW) remains a major public health problem because it contributes substantially to neonatal morbidity and mortality. Maternal factors, including age, nutritional status, and anemia, are considered important determinants of fetal growth and birth weight. This study aimed to analyze the association between maternal age, nutritional status, and anemia with the occurrence of low birth weight at Haji General Hospital Medan. A quantitative analytical study with a case-control design was conducted using secondary data obtained from medical records of mothers who delivered between January and December 2025. The study included 64 respondents, consisting of 32 mothers who delivered infants with low birth weight (cases) and 32 mothers who delivered infants with normal birth weight (controls). Cases were selected using total sampling, whereas controls were selected through simple random sampling. Data were analyzed using Chi-square tests with odds ratios (OR) and 95% confidence intervals (CI). The results showed that maternal age (<20 or >35 years) was significantly associated with low birth weight (OR = 4.259; 95% CI = 1.488–12.192; p = 0.006). Abnormal maternal body mass index (BMI <18.5 or ≥25 kg/m²) was also significantly associated with low birth weight (OR = 5.952; 95% CI = 1.977–17.920; p = 0.001), while maternal anemia increased the likelihood of low birth weight (OR = 3.645; 95% CI = 1.299–10.226; p = 0.012). Maternal age, nutritional status, and anemia were significantly associated with low birth weight. Strengthening antenatal care through early risk assessment, nutritional monitoring, and anemia prevention is essential to reduce the incidence of low birth weight..